Ulwembu : a play - McGarr, Dylan; Coppen, Neil; Mthombeni, Mpume; Urban Futures Centre; Big Brotherhood; Empatheatre (Baltimore, Maryland : Project Muse, 2018)
Evil stalks the township of KwaMashu, near Durban. It comes in the form of Whoonga, a toxic mix of Bgrade heroin, rat poison and other chemical components that almost immediately sucks its users into the vortex of addiction and the crime, deception and personal tragedy that goes with it. Caught up in the web, the ulwembu of the title, presided over by the dealer, Bongani Mseleku, are Lieutenant Portia Mthembu, a police officer in the frontline of the fight against the scourge; her son Sipho; his friend, Andile Nxumalo, and Emmanuel Abreu, a Mozambiqueborn spaza shopkeeper. As it traces Sipho's descent from talented scholar and aspirant poet and songwriter to suicidal addict, Ulwembu explores the effects of addiction not only on those who suffer from it but on communities, families and the police, both those who try to control the murderous trade and those who benefit from it. Using a process they have dubbed Empatheatre, The Big Brotherhood, Neil Coppen, Dylan McGarry and Mpume Mtombeni, aim to share 'people's reallife stories, with the intention to inspire and develop a greater empathy and kindness in spaces where there is conflict or injustice'. Ulwembu is the dramatic result of their efforts.
Print version record.
Added to collection customer.56279.3
Keywords: Drug abuse -- South Africa -- Durban -- Drama; DRAMA -- General; DRAMA -- English, Irish, Scottish, Welsh; Drug abuse; South Africa -- Durban; Electronic books; Drama